A synthetic chronogenetic gene circuit for programmed circadian drug delivery - Lara Pferdehirt; Anna R. Damato; Kristin L. Lenz; Maria F. Gonzalez-Aponte; Daniel Palmer; Qing-Jun Meng; Erik D. Herzog; Farshid Guilak (Nature Communications)
Abstract Circadian medicine, the delivery of therapeutic interventions based on an individual’s daily rhythms, has shown improved efficacy and reduced side-effects for various treatments. Rheumatoid arthritis and other inflammatory diseases are characterized by diurnal changes in cytokines, leading to inflammatory flares, with peak disease activity in the early morning. Using a combination of synthetic biology and tissue engineering, we developed circadian-based gene circuits, termed “chronogenetics”, that express a prescribed transgene downstream of the core clock gene promoter, Period2 (Per2). Gene circuits were transduced into induced pluripotent stem cells that were tissue-engineered into cartilage constructs. Our anti-inflammatory chronogenetic constructs produced therapeutic concentrations of interleukin-1 receptor antagonist in vitro. Once implanted in vivo, the constructs expressed circadian rhythms and entrained to daily light cycles, producing daily increases in biologic drug at the peak of Per2 expression. This approach represents the development of a cell-based chronogenetic therapy for various applications in circadian medicine.